The Role of Omnichannel Strategy in Enhancing Consumer Experience: A Literature Review - Willma Fauzzia; Agus Rahayu; Heny Hendrayati (Dinasti International Journal of Education Management And Social Science, 2025)
Omnichannel strategies have become key in enhancing consumer experience by creating integrated and seamless interactions across multiple channels. This research highlights the key factors that contribute to the success of omnichannel strategies, including channel integration, personalization, and experience consistency. Channel integration allows consumers to seamlessly switch between online and offline channels, while personalization provides relevant experiences according to individual preferences. Consistency in communication and offerings across channels plays an important role in building customer trust and loyalty. Implications for business practice suggest that companies need to invest in technological infrastructure and human resource training to support effective implementation of omnichannel strategies. This study also suggests that future research explore the integration of new technologies and the challenges faced in implementing omnichannel strategies, as well as their impact on customer loyalty and company profits. Thus, omnichannel strategies not only improve consumer experience, but also provide a sustainable competitive advantage in the digital age.